LELANG EKSEKUSI HAK TANGGUNGAN PADA PERBANKAN SYARIAH MENURUT HUKUM POSITIF DAN FIQH MUAMALAH - Husni Kamal (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2020)
The purpose of this research is to find out the execution auction conducted by sharia banks at KPKNL in Banda Aceh and the execution auctions according to a review of positive and Fiqh law. These types of research using descriptive analysis are describing and analyzing the auction-related execution. In conclusion, according to the positive law of the execution auction conducted by sharia banks in KPKNL already in accordance with the prevailing requirements and regulations, while according to the Fiqh rulings in the implementation there is still the occurrence of fraud committed by the auction mafia during the execution process of KPKNL that will affect the creditor on the sale of objects of liability.